Ensuring Responsive Action and Program Policy for Early Childhood Development and Education with Real-time Data Management - sudirman, sudirman; Wibowo, Lindawati; Apriatni, Mandri; Muadz, Husni; Sayuti, Rosiady; Prado, Elisabet; Shankar, Anuraj (Tirai Edukasi : Jurnal Pendidikan, 2019)
Objectives At West Nusa Tenggara, data were scattered in various sectors and yet no real-time data management was set up in the time of the study. We reported the staging of process on designing an applicable real-time data management system within a provincial program to support child growth, development and education. Materials and Methods A formative study was carried out to gather necessary information through data mapping, in-depth interviews with key stakeholders, document reviews, and direct field observations on infrastructures. Results and Findings To obtain a full picture on child growth, development and education, data from various sectors and programs shall be mapped and linked in one Platform. We introduce the Open Smart Registry Platform (OpenSRP) to systematically compile the individual as well as group data (i.e. village or district profiles) across different aspects of child life, ranging from nutrition, health, education, etc. Using a tablet PC, data could be easily entered at anytime (real-time data) by the person in charge into Enketo form - a user friendly application developed by Ona Systems. Due to still poor infrastructure at the grass root level, the system also allows a safety store offline that could automatically link to server when network connection is available. The immediate data entry will provide real-time data report that could be accessed by any relevant stakeholders at any levels to response accordingly. However, to avoid misuse of data, the access will also be restricted with a secured login system. Conclusion Based on the formative study, the OpenSRP is easily applicable for real-time data management given the local setting.